Design And Develop Academic Tutor Online Application System For FCSHD - Voon, Yu Wei (Universiti Malaysia Sarawak (UNIMAS), 2019)
This report is about the develop and design of academic tutor online application system . The main objective of this research is to simplifies the recruitment process. In the meanwhile, the specific objectives of the online application system provides lecturer to recruit academic tutor and evaluate the candidates online. Besides, students can view the job list and apply for the lab tutor job position through the online system. Before the development process of this online application system was conducted, the existing online e-recruitment system that is related to this application are reviewed to gather the features and, functionalities that are suitable and practicable. After that, the requirements has been analyzed and. fr-om the requirement gathered the system has been designed to make sure that the development process carry out systematically. In brief the academic tutor online application system is to simplify the recruitment process by reducing the time consumed and brings convenience for lecturers and students.